Tingkat Kondisi Fisik Atlet Bolavoli Putri Klub BPC - Ayu Permata Sari; Umar Umar; Alnedral Alnedral; Romi Mardela (Jurnal Patriot, 2021)
The problem in this research is that the athletes have not had a good physical condition. The low performance of athletes has decreased from year to year. The aim of the study was to see how the Physical Condition Level of Women's Volleyball Athletes at the BPC Tanah Datar Regency club. This type of research is quantitative using descriptive methods. The population in the study amounted to 16 people. The sampling technique used purposive sampling, thus the number of samples in the study were 12 female volleyball athletes at the BPC club Tanah Datar Regency. The data analysis technique is a percentage. Research result ; (1) The aerobic endurance in the category is sufficient with an average of 23.3 ml / kg.bb / m or about 41.67%, (2) the explosive power of the arm muscles in the less category with an average of 5.5 m or about 25%, (3) The explosive power of the leg muscles that is currently owned is in the low category with an average of 63 kg-m / second or about 33.33%, (4) the agility possessed is classified as in the medium category with an average of 9 seconds or about 25%, (5) The flexibility of the waist that is owned is classified in the less category with an average of 12.08 cm or about 33.33%, thus it can be concluded that the physical condition of women's volleyball athletes is good from indicators, power endurance, leg muscle explosive power, arm muscle explosive power, agility, and flexibility, are still in the low category and need to be improved to be higher.